SPECIATION AND SOLUBILITY OF HEAVY METALS IN CONTAMINATED SOIL USING X-RAY MICROFLUORESCENCE, EXAFS SPECTROSCOPY, CHEMICAL EXTRACTION, AND THERMODYNAMIC MODELING - Kirpichtchikova T.A.; Manceau A.; Spadini L.; Panfili F.; Marcus M.A.; Jacquet T. (My University, 2006)
Synchrotron-based X-ray radiation microfluorescence (μ-SXRF) and micro-focused and powder extended X-ray absorption fine structure (EXAFS) spectroscopy measurements, combined with desorption experiments and thermodynamic calculations, were used to evaluate the solubility of metal contaminants (Zn, Cu, Pb) and determine the nature and fractional amount of Zn species in a near-neutral pH (6.5-7.0) truck-farming soil contaminated by sewage irrigation for one hundred years. Zn is the most abundant metal contaminant in the soil (1103 mg/kg), followed by Pb (535 mg/kg) and Cu (290 mg/kg). The extractability of Zn, Pb, and Cu with citrate, S,S-ethylenediaminedisuccinic acid (EDDS), and ethylenediaminetetraacetic acid (EDTA) was measured as a function of time (24 h, 72 h, 144 h), and also as a function of the number of applications of the chelant (5 applications each with 24 h of contact time). Fifty-three percent of the Zn was extracted after 144 h with citrate, 51% with EDDS and 46% with EDTA, compared to 69, 87, and 61% for Cu, and 24, 40, and 34% for Pb. Renewing the extracting solution removed more of the metals. Seventy-nine, 65, and 57% of the Zn was removed after five cycles with citrate, EDDS and EDTA, respectively, compared to 88, 100, and 72% for Cu, and 91, 65, and 47% for Pb. Application to the untreated soil of μ-SXRF, laterally resolved μ-EXAFS combined with principal component analysis, and bulk averaging powder EXAFS with linear least-squares combination fit of the data, identified five Zn species: Zn-sorbed ferrihydrite, Zn phosphate, Zn-containing trioctahedral phyllosilicate (modeled by the Zn kerolite, Si4(Mg1.65Zn1.35)O10(OH) 2 · nH2O), willemite (Zn2SiO4), and gahnite (ZnAl2O4), in proportions of ~30, 28, 24, 11, and less than 10%, respectively (precision: 10% of total Zn). In contrast to Cu and Pb, the same fractional amount of Zn was extracted after 24 h contact time with the three chelants (40-43% of the initial content), suggesting that one of the three predominant Zn species was highly soluble under the extraction conditions. Comparison of EXAFS data before and after chemical treatment revealed that the Zn phosphate component was entirely and selectively dissolved in the first 24 h of contact time. Preferential dissolution of the Zn phosphate component is supported by thermodynamic calculations. Despite the long-term contamination of this soil, about 79% of Zn, 91% of Pb, and 100% of Cu can be solubilized in the laboratory on a time scale of a few days by chemical complexants. According to metal speciation results and thermodynamic calculations, the lower extraction level measured for Zn is due to the Zn phyllosilicate component, which is less soluble than Zn phosphate and Zn ferrihydrite. © 2006 Elsevier Inc. All rights reserved.